EFFECT OF POLYMER CONCENTRATION ON INITIAL MODEL PARAMETERS AND RHEOLOGICAL PROPERTIES OF BENTONITE/POLYMER DRILLING FLUID - Truong, Nguyen Huu (Vietnam Journal of Marine Science and Technology, 2017)
Bentonite/polymer fluid systems are often used to drill wells in the top of basement formation of the continental shelf of Vietnam, where the formation pressure gradient gradually reaches to subnormal pressure. Thus, bentonite/polymer drilling fluids with the mud weight from 8.4 ppg to 8.5 ppg are able to drill this section. In this study, the effect of the polymer concentrations on the initial parameters of the drilling fluid models have been presented in the detail of the article. Moreover, non-Newtonian fluid models often describe the behavior of fluids, which the models as Bingham plastic, Power law, Casson model, Herschel Bulkley, and Robertson-Stiff have mentioned. To determine the initial parameters of the models, the mathematical least square method is used. The database was gathered from 6 dial readings as 600 rpm, 300 rpm, 200 rpm, 6 rpm and 3 rpm of API 13B standard. Finally, the ANOVA table analysis shows that the confident coefficient reaches 100%, which has been demonstrated to be highly significant by the models.